Original paper The risk of depression in chronic obstructive pulmonary disease - Pietras, Tadeusz; Witusik, Andrzej; Panek, Michał; Górski, Paweł; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Chronic obstructive pulmonary disease is a severe systemic disease compromising to a large extent the quality of life due to dyspnea, recurrent infections, life-threatening conditions, considerable impairment of the patient’s social activity. Additionally, systemic inflammation accompanying the disease may affect central neurotransmission, thus contributing to the development of depression. Aim: The aim of the research was to assess the risk of mood disturbances in COPD patients as well as to estimate the risk level according to severity of the disease. Material and methods : The study was carried out on 174 patients with COPD and 121 healthy patients. All of them underwent spirometry to assess the flow-volume curve and to determine the severity of COPD according to the GOLD standard, as well as psychiatric examinations to diagnose depression episodes. Each patient was also assessed with the Beck Depression Inventory. Results : The relative risk of mood disturbances in COPD patients as compared with subjects without COPD was estimated to amount to 2.7007 (95% CI 1.3167-5.5393). Additionally, the increase of risk of mood disturbances in patients with first grade disease severity vs. healthy controls and patients with second grade disease severity vs. controls did not reach statistical significance – the obtained results were: 0.8219 (95% CI 0.2911-2.3202) and 1.5909 (0.5794-4.3683), respectively. For third grade COPD severity patients vs. healthy controls, the relative risk was estimated at 5.000 (95% CI 1.8766-13.3223) and was statistically significant, similarly to fourth grade severity patients vs. the control group (OR 20, 95% CI 6.6654-60.0112). The mean level of depression in the group of COPD patients was 8.51 ±4.18, in the group without COPD – 7.19 ±3.67; the difference was significant statistically (p = 0.005637). For patients with first grade disease severity, the mean score obtained according to the Beck Depression Inventory was 7.27 ±2.83, for second grade severity – 7.58 ±4.35, for third grade – 10.26 ±3.99, and for the fourth grade – 12.57 ±5.20. The coefficient of correlation between the results of the Beck Depression Inventory and FEV1 percentage values as compared with normal FEV1 obtained for the overall population of COPD patients was negative: r = –0.466011, p = 0.000. Conclusions : Development of chronic obstructive pulmonary disease increases the relative risk of a depression episode. This risk increases with the increase of disease severity assessed according to the GOLD grading standard.